Patients' expectations and solutions for improving primary diabetes care. Issue 6 (14th August 2017) - Vachon, Brigitte; Huynh, Ai-Thuy; Breton, Mylaine; Quesnel, Louise; Camirand, Michel; Leblanc, Jeannette; Tardif, Sylvie
Abstract : Purpose: The purpose of this paper is to document health care needs expressed by people living with diabetes, describe the solutions they envisaged for improving the quality of primary care (PC) services and empower them to make better use of PC services. Design/methodology/approach: A participatory research approach was used. Six workshops were organised to provide diabetes patients with knowledge on available services and to engage them in sharing their experience. Group discussions were recorded. Data were analysed using the thematic analysis method. Findings: In total, 79 persons living with diabetes for a mean of 13 years participated. Needs expressed were grouped under seven themes: assurance of satisfactory follow-up by a family physician, continuous access to services adapted to evolving needs, motivation to adopt and maintain healthy behaviours, maintenance of knowledge about diabetes, psychological support, financial constraints, and collaboration with secondary-level services. Patients proposed solutions for improving services that were grouped under five themes: facilitating access to services, disseminating information about available services, centralising diabetes information on the internet, offering personalised services and improving interprofessional collaboration. Practical implications: Needs expressed by diabetic patients concern different aspects of care such as accessibility, organisation, coordination, and better dissemination and visibility of services. The solutions proposed by patients focussed on better access to information and interprofessional services. Originality/value: The workshop format used in this study offers an original and interesting approach and tool for actively engaging patients in quality improvement of services.